Pendidikan Karakter Profil Pelajar Pancasila Melalui Pembelajaran IPS Berbasis Islam Terapan - Sulaswari, Misroh; Handoyo, Eko (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2023)
This study aims to develop ideas related to strengthening character education according to the Pancasila Student Profile which is integrated in social studies learning. Applied Islam-based social studies learning is an integration of social studies material with the values of the Islamic religion that are adapted to the six dimensions in the Pancasila student profile, namely faith, piety to God and noble character, global diversity, mutual cooperation, independence, critical reasoning, and creativity. Through a literature study on the theory of the relation of science and religion, Barbour and Wilber Serts collected several relevant previous studies which were then used as an analytical tool to find formulas for character education in social studies learning. The findings show that the idea of Applied Islamic Social Studies Learning in strengthening Pancasila profile character education can be carried out by internalizing the Islamic religious values related to IPS material. The six dimensions in the Pancasila student profile form the basis for social studies learning by constructing learning materials according to Islamic religious values. Students are not only equipped with cognitive abilities but also instilled attitudes and skills so that character is realized according to the Pancasila student profile.